Retinal Degeneration in MPS-IIIA Mouse Model - Intartaglia, Daniela; Giamundo, Giuliana; Marrocco, Elena; Maffia, Veronica; Salierno, Francesco Giuseppe; Nusco, Edoardo; Fraldi, Alessandro; Conte, Ivan; Sorrentino, Nicolina Cristina (Frontiers in Cell and Developmental Biology, 2020)
Mucopolysaccharidosis type IIIA (MPS-IIIA, Sanfilippo A) is one of the most severe lysosomal storage disorder (LSD) caused by the inherited deficiency of Sulfamidase, a lysosomal sulphatase enzyme involved in the stepwise degradation of heparan sulphates (HS). MPS-IIIA patients show multisystemic problems, including a strong impairment of central nervous system (CNS), mild somatic involvement and ocular manifestations that result in significant visual impairment. Despite the CNS and somatic pathology have been well characterized, studies on visual system and function remain partially explored. Here, we characterized the retina morphology and functionality in MPS-IIIA mouse model and analyzed how the SGSH deficiency affects the autophagic flux. MPS-IIIA mice exhibited a progressive retinal dystrophy characterized by significant alterations in visual function. The photoreceptor degeneration was associated with heparan sulphate accumulation and a block of autophagy pathway. These events caused a reactive microgliosis, and a development of apoptotic processes in MPS-IIIA mouse retina. Overall, this study provides the first phenotypic spectrum of retinal disorders in MPS-IIIA and significantly contributes for diagnosis, counseling, and potential therapies development.